Suggestopedia: use and revirw of the technique and steps to be applied in an efl clasroom - Albán Rodríguez, María Belén
This research has been done through an analytical and critical process, whose main objective is review the uses and steps used in Suggestopedia method to be applied in an EFL classroom. Suggestopedia approach is a set of techniques designed to help students relax and get ready for the class through the use of Suggestion which means to break the students? psychological barriers and fulfill them with positive attitudes. This approach uses different techniques of relaxation, environment set-up, peripheral learning, authority, presentation of the linguistic material, follow- up activities, error correction, homework and evaluation which are divided in three main stages presentation, concert and practice. In the same way, this works offers a practical guide about the better uses of Suggestopedia into our local setting as an important device in the teaching of a foreign language.